ANTIOXIDANT ACTIONS OF AMINO CHROMENE PRODUCTS WITH ALKYL TAIL: SYNTHESIS AND CHARACTERISATION - Madasamy Kumar, Veerappan Jeyachandran (International Journal of Modern Agriculture, 2020)
The reaction between substituted 4-hydroxy benzaldehyde, active methlyene compounds and resorcinol yield amino chromene derivatives. Structures of these were established upon the basis of IR, 1HNMR, 13CNMR, and MASS data. In vitro, antioxidants activities of these compounds against super oxide anion radical, nitric oxide radical, DPPH radical and hydrogen peroxide were evaluated and compared with standard natural antioxidants ascorbic acid.